2009
DOI: 10.1182/blood.v114.22.4317.4317
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Hematopoietic Stem Cell Transplantation From An Emerging Centre in North India.

Abstract: 4317 Introduction With a huge burden of hematological and oncological disorders for which hematopoietic stem cell transplant (HSCT) is a curative option, India saw the development of HSCT program from 1986 onwards. Since then, some 10 centres have performed over 1600 transplants until the year 2005, including one-third in thalassemic patients. However, current HSCT facilities are still limited and cannot address the treatment needs of the immense patient load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…In western countries, long-term survival was reported as 50-70% in chronic leukemias and 80-90% with aplastic anemias [8]. The overall mortality rate reported in the present study is in accordance with the previous studies wherein mortality rate ranges from 13.7-40.0% [8][9][10][11].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In western countries, long-term survival was reported as 50-70% in chronic leukemias and 80-90% with aplastic anemias [8]. The overall mortality rate reported in the present study is in accordance with the previous studies wherein mortality rate ranges from 13.7-40.0% [8][9][10][11].…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have reported concordant observation suggesting infection and GvHD post-HSCT as major risk factors of mortality [8,10,12]. In a retrospective study from North India reported different reasons of death including sepsis, GvHD, and sinusoidal obstruction syndrome [11]. A study by Nair et al reported mortality rate of 37.7% in patients who underwent allogenic transplantation and GvHD, infections and relapse were the common reasons for death of patients [13].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In another study from India, which also included adult patients with multiple myeloma, Yadav et al demonstrated a 55.6% OS at a median follow-up of 114 days (range: 21-617 days). The median duration of neutrophil engraftment in their study was 12 days (range, 9-30) 17 . Relapsed/refractory HL had a 5-year OS of about 68% 18 and in HR NB, an EFS of 50% has been demonstrated by Landenstein et al in patients undergoing ASCT with BuMel conditioning 19 .…”
Section: Discussionmentioning
confidence: 93%